Selected Papers from the XXI SPB National Congress of Biochemistry 2021 - Manuel Aureliano; M. Leonor Cancela; Ana R. Costa; Célia M. Antunes (BioChem, 2025)
The XXI SPB National Congress of Biochemistry 2021 was held at the University of Évora in Portugal on 14–16 October 2021 [...]